2018
DOI: 10.1002/chir.22838
|View full text |Cite
|
Sign up to set email alerts
|

Circularly polarized luminescence of helically assembled pyrene π‐stacks on RNA and DNA duplexes

Abstract: In this report, we describe the circularly polarized luminescence (CPL) of the RNA duplexes having one to four 2'-O-pyrene modified uridines (Upy) and the DNA duplexes having two, four, and six pyrene modified non-nucleosidic linkers (Py). Both the pyrene π-stack arrays formed on the RNA and DNA double helical structures exhibited pyrene excimer fluorescence. In the pyrene-modified RNA systems, the RNA duplex having four Upys gives CPL emission with g value of <0.01 at 480 nm. The structure of pyrene stacks on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…Chiral ions or ionic molecules are attractive owing to their asymmetric catalytic activity, 1–4 enantioselectivity, 5 or their chiroptical properties 6,7 . Chiral co‐crystallization, 8 chiral molecular assemblies, 9–15 or confinement of achiral ions in chiral cyclodextrins 16 can be used to induce chiroptical properties to achiral ions or molecules and/or enhancing chiral signals with promising advantages such as (1) tunability of the chiral properties, (2) versatility of choices of chromophores (molecules, ions particles, etc. ), and (3) transparency of solutions in the UV–vis region due to the nanometric size of the assemblies.…”
Section: Introductionmentioning
confidence: 99%
“…Chiral ions or ionic molecules are attractive owing to their asymmetric catalytic activity, 1–4 enantioselectivity, 5 or their chiroptical properties 6,7 . Chiral co‐crystallization, 8 chiral molecular assemblies, 9–15 or confinement of achiral ions in chiral cyclodextrins 16 can be used to induce chiroptical properties to achiral ions or molecules and/or enhancing chiral signals with promising advantages such as (1) tunability of the chiral properties, (2) versatility of choices of chromophores (molecules, ions particles, etc. ), and (3) transparency of solutions in the UV–vis region due to the nanometric size of the assemblies.…”
Section: Introductionmentioning
confidence: 99%
“…The circular dichroism​ (CD) signals of DNA generally appear in the ultraviolet range . CPL can be induced by pyrene π-stack arrays formed on chemically modified DNA double helical structures, but laborious synthetic procedures are required to obtain this modified molecule . We hypothesized that DNA molecules would behave as a unique chiral template for fluorophore binding: that DNA’s natural chirality can be transferred to the bound dye molecules, triggering CPL activity from the coassemblies.…”
mentioning
confidence: 99%
“…They include decorating inorganic quantum dots with suitable modified aminoacids, [ 27 ] and introducing pyrene π‐stack arrays formed on chemically modified DNA double helical structures. [ 28 ]…”
Section: Discussionmentioning
confidence: 99%
“…They include decorating inorganic quantum dots with suitable modified aminoacids, [27] and introducing pyrene π-stack arrays formed on chemically modified DNA double helical structures. [28] Jiang et al has recently and elegantly demonstrated the power of fabricating biological structures with CPL emissive synthetic dyes and applied the assembly for DNA sensing. [29] The rationale behind the approach is that DNA molecules can behave as unique chiral templates for fluorophores; DNA's natural chirality can be transferred to the bound dye molecules, triggering CPL activity from the assembly.…”
Section: Bioinspired Assembliesmentioning
confidence: 99%